Pemberdayaan Pemuda Desa Tapaluluo melalui Kegiatan Permainan Bola Voli - Mile, Sarjan; Datau, Suriyadi; Ruslan, Ruslan; Parengkuan, Meyke; Isnanto, Juni; Amri, Muh. Faisal Lutfi; Pratama Diuli, Muhammad Reza; Nagi, Julkifli S.U (-, 2026)
This community service activity aims to empower rural youth through volleyball activities as a means of increasing sports participation, character development, and strengthening social cohesion. Volleyball was selected because it is easy to implement, widely favored by the community, and possesses educational as well as recreational value. The implementation methods include program socialization, training on basic volleyball techniques, mentoring of regular practice activities, and evaluation of the program outcomes. The results indicate an increase in rural youths’ enthusiasm for sports participation, improvement in basic volleyball skills, and the development of values such as teamwork, discipline, and sportsmanship. This activity is expected to serve as a sustainable model for rural youth empowerment through sports.